The effect of emigration on child labor - Gil S. Epstein; Nava Kahana (Institute for the Study of Labor (IZA), 2007)
We present a general model of child labor that incorporates the various components presented in the literature as explanations for its existence. Our proposal is to mitigate the phenomenon by encouraging temporary emigration. It emerges that the remittances sent by the emigrating parents might enable not only their children, but also others, to stop working. We show how this equilibrium can be sustained even upon the return of the emigrant parents to their home country.
Keywords: 330; Child labor; temporary emigration; Kinderarbeit; Haushaltsökonomik; Eltern; Internationale Arbeitsmobilität; Rücküberweisung (Migranten); Theorie